Comparison of the sensitivity of patient-reported outcomes for detecting the benefit of biologics in severe asthma. (10th September 2021) - Hyland, Michael E; Lanario, Joseph W; Menzies-Gow, Andrew; Mansur, Adel H; Dodd, James W; Fowler, Stephen J; Hayes, Gemma; Jones, Rupert C; Masoli, Matthew
Background: The sensitivity of patient-reported outcomes (PROs) to detect the effects of treatment change depends on the match between the change in items of the PRO and the change that takes place in a sample of people. The aim of this study is to compare the sensitivity of different PROs in detecting changes following the initiation of biologic treatment in asthma.Methods: Patients starting a biologic treatment as part of clinical care completed the Asthma Control Questionnaire (ACQ-6), the Severe Asthma Questionnaire (SAQ and SAQ-global scores) and the EQ5D (EQ-5D-5L and EQ5D-VAS) at baseline. They completed the ACQ-6, SAQ, SAQ-global and a retrospective global rating of change (GRoC) scale at weeks 4, 8 and 16 and completed the EQ-5D-5L and EQ5D-VAS at week 16. The SAQ-global and EQ5D-VAS differ but both are single item 100-point questions. Sensitivity was measured by Cohen's D effect size at each of the three time points.Results: 110 patients were recruited. Depending on the time of assessment, effect size varied between 0.45 and 0.64 for the SAQ, between 0.50 and 0.77 for the SAQ-global; between 0.45 and 0.69 for ACQ-6; between 0.91 and 1.22 for GRoC; 0.32 for EQ-5D-5L and 0.49 for EQ5D-VAS.Conclusion: The sensitivity to change of a questionnaire varies with the time of measurement. The three asthma-specific prospective measures (SAQ, SAQ-global and ACQ-6) have similar sensitivity to change. The single-item EQ5D-VAS was less sensitive than the asthma specific measures and less sensitive than the single-item SAQ-global. The EQ-5D-5L was least sensitive.